A language academy by any other name(s): the case of Croatia - Langston, Keith (Array, 2011)
There are three main institutions in Croatia today that are actively engaged in language management activities on the national level: The Croatian Academy of Sciences and Arts, The Council for the Norms of the Croatian Standard Language, and the Institute for the Croatian Language and Linguistics. Their efforts are focused on establishing the status of Croatian as a separate language in its own right, as historically and culturally distinct from Serbian and other related language varieties, and on corpus planning to further differentiate Croatian from these neighboring varieties. After providing some background information on the institutions in question and the historical and political context, the authors discuss language policy and planning in Croatia from the time of its independence in 1991 to the present and argue that these three institutions share a number of features with prototypical examples of language academies and are functionally equivalent to such institutions, although they do not bear this name.